Small Intestine Microbiome and Metabolome of High and Low Residual Feed Intake Angus Heifers - Liu, Yue; Liu, Chang; Wu, Hao; Meng, Qingxiang; Zhou, Zhenming (Frontiers in Microbiology, 2022)
The gastrointestinal tract (GIT) contains complex microbial communities and plays an essential role in the overall health of the host. Previous studies of beef cattle feed efficiency have primarily concentrated on the ruminal microbiota because it plays a key role in energy production and nutrient supply in the host. Although the small intestine is the important site of post ruminal digestion and absorption of nutrients, only a few studies have explored the relationship between the microbial populations in the small intestine and feed efficiency. Moreover, variations in GIT metabolites contribute to differences in feed efficiency. The objective of this study was to investigate relationships among bacterial populations of duodenum, jejunum, ileum; microbial metabolites; and RFI phenotype of beef cattle. We carried out by using Illumina MiSeq sequencing of the 16S rRNA V3-V4 region and liquid chromatography-mass spectrometry (LC-MS). In the duodenum, the relative abundances of Firmicutes (P < 0.01), Lachnospiraceae, Ruminococcaceae, Family_XIII, Christensenellaceae, Christensenellaceae_R-7_group (P < 0.05), and Lachnospiraceae_NK3A20_group (P < 0.05) were higher in the low residual feed intake (LRFI) group compared with the high residual feed intake (HRFI) group, whereas the HRFI group had higher abundances of Proteobacteria and Acinetobacter (P < 0.01). In the jejunum, the relative abundances of Lachnospiraceae and Lachnospiraceae_NK3A20_group were higher in the LRFI group (P < 0.05). In the ileum, the relative abundances of Ruminococcaceae (P < 0.01), Christensenellaceae, Christensenellaceae_R-7_group, and Ruminococcus_2 were also higher in the LRFI group (P < 0.05). Moreover, the genera Lachnospiraceae_NK3A20_group, Christensenellaceae_R-7_group, and Ruminococcus_2 were negatively associated with RFI, while the genus Acinetobacter was positively associated with RFI. The metabolomics analysis revealed that the LRFI group significantly improved protein digestion and absorption, as well as glycerophospholipid metabolism in the duodenum, jejunum, ileum. The correlation between intestinal microorganisms and metabolites revealed that some microorganisms play an important role in amino acid metabolism, glycerophospholipid metabolism, nutrient digestion and absorption, and antioxidant enhancement. The present study provides a better understanding of the small intestinal microbiota and metabolites of beef cattle with different RFI phenotypes and the relationships among them, which are potentially important for the improvement of beef cattle feed efficiency.